Locating politics in Ethiopia's Irreecha ritual - Debele, Serawit (Leiden Boston Brill, 2019)
Introduction -- Irreecha at Hora Arsadi -- Oromumma: Re/shaping Discourses -- Contestations -- The Making of the State -- Displacing the State -- Conclusion: Locating Politics in and of Irreecha
"Serawit Bekele Debele, Ph.D. (2015), BIGSAS/Bayreuth University, is a research fellow at the Max Planck Institute for the Study of Religious and Ethnic Diversity. She has published various articles and book chapters on religion and politics in contemporary Ethiopia, including "Reading Prayers as Political Texts: Reflections on Irreecha Ritual in Ethiopia", Politics, Religion & Ideology, 2018"
Literaturverzeichnis Seite [193] - 205
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Irreecha (Festival) -- Political aspects; Oromo (African people) -- Ethiopia -- Rites and ceremonies; Oromo (African people) -- Political activity; Religion And Politics -- Ethiopia; Ethiopia -- Religious life and customs; Ethiopia -- Politics and government -- 1991-